Peak exposure concentrations of dust and flour aeroallergen in flour mills and bakeries. - Nieuwenhuijsen, M; Sandiford, C; Lowson, D; Tee, R; Venables, K; Newman Taylor, A (1995)
As part of an epidemiological study amongst workers exposed to flour we measured peak exposure levels to total dust and flour aeroallergen with personal samplers in bakeries, flour mills and packing stations. Short-term tasks which were expected to give rise to high concentrations of exposure (peaks) were identified. The frequency and duration of these tasks were estimated and their levels of exposure to dust and flour aeroallergen measured. In total 209 samples were taken. The highest exposure concentrations both for dust (geometric mean > 30 mg m-3) and for flour aeroallergen (geometric mean > 500 micrograms m-3) were measured during certain operations. Exposure concentrations for the tasks were often much higher than the levels we had measured over a shift in a previous study. This might be important for sensitization and for the development of asthma. Peak exposure concentrations could be used to explore the exposure-response relationship more comprehensively. In general average flour aeroallergen concentrations increased linearly with average dust concentrations, although there were some exceptions.